UPAYA PENINGKATAN MOTIVASI BERIBADAH PESERTA DIDIK - Akram Fadhlurrahman; Fathor Rohim; Dina Mardiana (Tarbiyatuna Kajian Pendidikan Islam, 2024)
This study aims to analyze the motivation of students in enhancing their worship motivation at MAN 1 Kupang. Islamic religious education is expected to play a significant role in increasing students' worship activities. The method used is qualitative with a case study approach. The sources of information include students, Islamic religion teachers, and the principal, as well as additional data from eleventh-grade students. Data collection was conducted through observation, interviews, and documentation to gain a deeper understanding of worship motivation. The analysis techniques employed include data reduction, data presentation, and conclusion drawing. The results indicate that efforts to enhance worship motivation are realized through worship programs, Dhuha prayers, and Dhuhr prayers. This motivation positively impacts students' worship activities, both in the school environment and outside of it. The study also refers to Abraham Maslow's hierarchy of needs theory, highlighting the importance of fulfilling psychological needs, safety, love, esteem, and self-actualization in encouraging students' worship motivation at MAN 1 Kupang